The Strategy of the School Principle in the Implementation of the Independent Curriculum - Nari, Nola; Khaidir, Christina; Arif, Yudabbirul; Gistituati, Nurhizrah; Rusdinal, Rusdinal; Intes, Amina (Lingeduca: Journal of Language and Education Studies, 2023)
This study aims to determine the role of the school principal as a change leader, the principal's strategy as a change leader, the principal's innovation as a change leader, the factors supporting change, and the factors inhibiting change in the implementation of an independent curriculum. This study uses a qualitative approach. Research informants were selected by purposive sampling technique. The data collection process was carried out by in-depth interviews, documentation studies and field notes. Data analysis was performed with reference to the Miles and Huberman model. To ensure the validity of the data, researchers used triangulation techniques and increased the persistence of researchers in analyzing the documents they found. The conclusions of this study are: (1) the role of the principal is shown by the implementation of the independent curriculum, driving the learner-centered learning process. and provide independence to work for students and educational staff; (2) the principal's strategy is by identifying cases, conducting interviews, creating good relations, and creating an atmosphere towards students' awareness of the implementation of the independent curriculum; (3) the innovation of the school principal in carrying out P5, entrepreneurship (traditional food bazaar), voting for democracy (election for the OSIS chairman) and building body and soul (religious activities such as the Ramadan Islamic boarding school); (4) Factors supporting the school principal, namely internal factors (infrastructure and leadership of the school principal) and external factors, namely there are already 2 driving force teachers resulting from training organized by the government; (5) Obstacles from internal parties, namely: lack of teacher education, There are teachers who are inconsistent in their implementation, there are teachers who are clueless.